2020
DOI: 10.1371/journal.pone.0215788
|View full text |Cite
|
Sign up to set email alerts
|

Alarm tones, music and their elements: Analysis of reported waking sounds to counteract sleep inertia

Abstract: Sleep inertia is a potentially dangerous reduction in human alertness and occurs 0-4 hours after waking. The type of sound people set as their alarm for waking has been shown to reduce the effects of sleep inertia, however, the elemental musical factors that underpin these waking sounds and their relationships remain unclear. The goal of this research is to understand how a particular sound or music chosen to assist waking may counteract sleep inertia, and more specifically, what elements of these sounds may c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(36 citation statements)
references
References 72 publications
5
31
0
Order By: Relevance
“…The results obtained from this study present new evidence for the potential of auditory alarms to effectively counteract the inhibiting symptoms of SI . Specifically, this study’s results support previous research showing a significant relationship between the reported melodicity of participants’ waking sound and a measure of perceived SI reduction (34).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The results obtained from this study present new evidence for the potential of auditory alarms to effectively counteract the inhibiting symptoms of SI . Specifically, this study’s results support previous research showing a significant relationship between the reported melodicity of participants’ waking sound and a measure of perceived SI reduction (34).…”
Section: Discussionsupporting
confidence: 88%
“…Awakening countermeasures have been researched in several contexts and themes, which may be considered as extensions or augmentations of ubiquitous human behaviours and routines. These include; caffeine (14, 2225), light (16, 24, 2628), temperature (29, 30), post-awakening routines (24, 31), sound (3234), and stress (35).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations